2014
DOI: 10.1007/s13105-014-0350-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega-3 fatty acids on haemostatic functions in urocortin-treated obese rats

Abstract: Urocortin 1 (UCN1) decreases food intake. We investigated the effects of UCN1 and omega-3 fatty acids (FA) on metabolic and coagulation parameters in high fat diet (HFD)-fed rats. Fifty male Sprague Dawley rats were divided into five groups; control, HFD, HFD with omega-3 FA, HFD with UCN1, and HFD with UCN1 and omega-3 FA. Food intake, body weight (BW), body mass index (BMI), Lee index, glucose, insulin, HOMA-IR, triglycerides, cholesterol, low (LDL) and high (HDL) density lipoproteins, fibrinogen, plasminoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
4
1
1
Order By: Relevance
“…APTT and PT were marginally shorter in the HFD-fed animals for both sexes. Contrary to previous studies (Kaji et al 2013; El-Gendy and Abbas 2014; Dallak et al 2018; Sakr, Abbas, and Haidara 2018), HFD-fed rats exhibited a decrease in both FIB and PLT counts, which may reflect a low-grade consumption of both parameters owing to a mild hypercoagulable state associated with chronic HFD feeding. These findings suggest that the HFD-fed animals may have a higher tendency for increased blood clotting.…”
Section: Discussioncontrasting
confidence: 99%
“…APTT and PT were marginally shorter in the HFD-fed animals for both sexes. Contrary to previous studies (Kaji et al 2013; El-Gendy and Abbas 2014; Dallak et al 2018; Sakr, Abbas, and Haidara 2018), HFD-fed rats exhibited a decrease in both FIB and PLT counts, which may reflect a low-grade consumption of both parameters owing to a mild hypercoagulable state associated with chronic HFD feeding. These findings suggest that the HFD-fed animals may have a higher tendency for increased blood clotting.…”
Section: Discussioncontrasting
confidence: 99%
“…5) in isoproterenolinduced rats. These results were in agreement with those of previous studies [8,25]. Moreover, the improvement of the serum TG by n-3 PUFA may explain the additive effect observed for ISOR + n-3 PUFA.…”
Section: Discussionsupporting
confidence: 93%
“…Group II included normal rats administered ISOR (10 −6 mol/L, in drinking water) [41] for 30 days. Group III included normal rats administered n-3 PUFA (0.3 g/kg/day by gavage) [8] for 30 days. Group IV animals (AMI) received isoproterenol (85 mg/kg body weight) intraperitoneally twice at an interval of 24 h on the 29th and 30th days.…”
Section: Experimental Designmentioning
confidence: 99%
“…Following these early results, several mechanistic studies of EPA and DHA and platelet function suggested diminished platelet aggregation, with a variety of proposed molecular mechanisms. 3743 These experimentally observed effects raised concern about a potential bleeding risk with fish oil supplements, 8, 11 which has led many health care providers and organizations to request that patients should stop taking fish oil for at least one week before surgery. 9, 10, 44, 45 This standard of practice can therefore delay patient care as well as increase hospital length of stay and cost.…”
Section: Discussionmentioning
confidence: 99%